Individual variations in cardiovascular-disease-related protein levels are driven by genetics and gut microbiome. (November 2018) - Zhernakova, Daria; Le, Trang; Kurilshikov, Alexander; Atanasovska, Biljana; Bonder, Marc; Sanna, Serena; Claringbould, Annique; Võsa, Urmo; Deelen, Patrick; Franke, Lude; de Boer, Rudolf; Kuipers, Folkert; et al.
Abstract Despite a growing body of evidence, the role of the gut microbiome in cardiovascular diseases is still unclear. Here, we present a systems-genome-wide and metagenome-wide association study on plasma concentrations of 92 cardiovascular-disease-related proteins in the population cohort LifeLines-DEEP. We identified genetic components for 73 proteins and microbial associations for 41 proteins, of which 31 were associated to both. The genetic and microbial factors identified mostly exert additive effects and collectively explain up to 76.6% of inter-individual variation (17.5% on average). Genetics contribute most to concentrations of immune-related proteins, while the gut microbiome contributes most to proteins involved in metabolism and intestinal health. We found several host–microbe interactions that impact proteins involved in epithelial function, lipid metabolism, and central nervous system function. This study provides important evidence for a joint genetic and microbial effect in cardiovascular disease and provides directions for future applications in personalized medicine. Genome-wide and metagenome-wide association study of 92 cardiovascular-diseases-related proteins identifies genetic and microbial factors that explain 76.6% of inter-individual variation, highlighting the role of gut microbiome in cardiovascular disease.